Further evidence supporting high diversity of cyathealean tree ferns in the Early Cretaceous of Antarctica - Vera, Ezequiel Ignacio (2015)
Two new specimens of a cyathealean fern stems collected from the Lower Cretaceous (Aptian) Cerro Negro Formation, which crops out at the South Shetland Islands, Antarctica, are described in detail. The specimens are dictyostelic stems with U-shaped meristeles without sclerenchyma sheaths and petiole bases with numerous, small, vascular strands, and a mantle of adventitious roots. The anatomy of the stems show similarities with Cibotiaceae, but given they are not well preserved, some critical features that would allow a conclusive referral to this family are lacking. Preserved in the surrounding matrix, fragmentary pinnules were found, showing sori with bivalvate indusia, and sporangia with more than 20 spores, attached to an elongate receptacle. The features observed in these fertile remains suggest cyathealean affinities, but are difficult to refer to a particular family. These findings increase the diversity of cyathealean tree ferns in the Cerro Negro Formation, supporting previously suggested warm climatic conditions for this region of Antarctica during the Aptian.